Agricultural furrow irrigation inefficiency in the basin of the Laguna de Bustillos, Chihuahua, Mexico: geometric characteristics of agricultural plots and aquifer depletion - Alatorre Cejudo, Luis Carlos (2019)
The objective of this research was to determine the relationship between the inefficiency of furrow irrigation, the geometric characteristics of agricultural plots and the depletion of the aquifer conditions of the Laguna Bustillos basin (Chihuahua, Mexico) in recent decades (1991-2012). The main results were: the analysis of geometric characteristics showed that the Mennonite properties have the least favorable conditions for the use of furrow irrigation; the index of inefficiency of furrow irrigation demonstrated the existence of agricultural plots that exceed 2.5 to 13 times the maximum allowed length; the analysis of the spatial and temporal evolution of the depletion of the aquifer showed that the areas with higher depletion (up to -80 m depth) are located mainly in Mennonite properties; it was shown that the index of inefficiency of furrow irrigation is directly related to the geometrical properties of agricultural plots and to the level of depletion of the aquifer. It is clear that reversing this problem will require a land use plan that includes the geometric reconfiguration of agricultural plots or the use of new technologies such as sprinkler and drip irrigation, as well as territorial strategies that increase the areas of natural and artificial recharge of the aquifer.